2012
DOI: 10.4018/jitpm.2012070104
|View full text |Cite
|
Sign up to set email alerts
|

Project-to-Organization Matching

Abstract: Recent studies show that the capacity of organizations to cope with risk is usually neglected in project risk analysis (see for instance Bannerman, 2008 in the context of software projects). Using single-dimension risk assessment approaches, vulnerability, or conversely competence of the organization, is not taken into account in the decision to or not to undertake a risky project. This paper proposes a two-dimensional multi criteria approach with the aim of providing a more complete risk assessment decision s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…Such a backward-looking forecasting ignores the new trends and highs and lows in different economic environments. Also, organizational factors, such as reputation and marketing strategies, as well as internal risks (related to availability of SCM resources), could greatly influence the demand [107] and thus contribute to inaccuracy of BDA-based demand predictions using historical data. Incorporating existing driving factors outside the historical data, such as economic instability, inflation, and purchasing power, could help adjust the predictions with respect to unseen future scenarios of demand.…”
Section: Predictive Bda Applicabilitymentioning
confidence: 99%
“…Such a backward-looking forecasting ignores the new trends and highs and lows in different economic environments. Also, organizational factors, such as reputation and marketing strategies, as well as internal risks (related to availability of SCM resources), could greatly influence the demand [107] and thus contribute to inaccuracy of BDA-based demand predictions using historical data. Incorporating existing driving factors outside the historical data, such as economic instability, inflation, and purchasing power, could help adjust the predictions with respect to unseen future scenarios of demand.…”
Section: Predictive Bda Applicabilitymentioning
confidence: 99%
“…It should be kept in mind that project can also have adverse effect on organizational business (Huemann et al, 2012). It has been observed that during the analysis of risk associated with project, it is often neglected to evaluate the risks that the proposed project can bring for an organization (Mafakheri, Breton & Chauhan, 2012). If a project is failed then organization will not be considered as good in that particular field by market.…”
Section: Importance Of Alignmentmentioning
confidence: 99%